The Impact of Law's History
XV, 304 p.
Keywords: This book considers how legal history has shaped and continues to shape our shared present. Each chapter draws a clear and significant connection to a meaningful feature of our lives today. Focusing primarily on England and Australia, contributions show the diversity of approaches to legal history’s relevance to the present. Some contributors have a tight focus on legal decisions of particular importance. Others take much bigger picture overview of major changes that take centuries to register and where impact is still felt. The contributors are a mix of legal historians, practising lawyers, members of the judiciary, and legal academics, and develop analysis from a range of sources from statutes and legal treatises to television programs. Major legal personalities from Edward Marshall Hall to Sir Dudley Ryder are considered, as are landmarks in law from the Magna Carta to the Mabo Decision. Sarah McKibbin is Lecturer (Law) in the School of Law and Justice, Universityof Southern Queensland, Australia, and co-author of A Legal History for Australia (2021) with Marcus Harmes and Libby Connors. Jeremy Patrick is Lecturer in the School of Law and Justice, University of Southern Queensland, Australia. He has published multiple journal articles on historical aspects in the area of law and religion, including constitutional religion clauses, blasphemous libel, and the legal regulation of fortune-telling and individual spirituality. He is author of Faith or Fraud: Fortune-telling, Spirituality, and the Law (2020). Marcus Harmes is Professor, Associate Director Research in the University of Southern Queensland College, Australia, and teaches legal history in the law degree. He has published extensively in the fields of religious and political history, with a particular emphasis on British religious history and constitutional history. .